Specificity of the refinancing of mortgage loans in Russia and conceptual approaches to them - A. V. Vlasov (Путеводитель предпринимателя)
The article considers the peculiarities of risk management in modern conditions. In the turbulence of the Russian economy and capital flight from the country, as well as the «flight» of foreign investors to the state authorities is a key task in creating a favorable environment for the development of innovative projects.